Women in the world a comparative study - Ross, Ruth A. 1933-; Iglitzin, Lynne B. 1931- (Studies in comparative politics, 1976)
"This volume is the result of a series of seminar meetings sponsored jointly by the Department of Political Science of the University of California, Santa Barbara, and the Center for the Study of Democratic Institutions."